Right to respect for private and family life, home and correspondence : a practical guide to the Article 8 case-law of the European Court of Human Rights / Päivi Hirvelä, Satu Heikkilä. - Hirvelä, Päivi; Heikkilä, Satu (Intersentia, 2023)
This text provides a comprehensive, detailed and up-to-date account of Strasbourg case-law on Article 8 of the European Convention on Human Rights. It focuses on the Court's most important cases on private and family life, home and correspondence, which have been selected following the Court's Jurisconsult's opinion of their jurisprudential interest.